KAUSALITAS NILAI TUKAR DAN EKSPOR INDONESIA: SEBELUM DAN MASA PANDEMI COVID-19 - Lusiana Puspa Citra Rini; Yustinus Wahyudi (Universitas Gunadarma, 2023)
The weakening of the exchange rate (Rupiah USD) in Indonesia before the pandemic and the fluctuating exchange rate during the pandemic did not show an impact on the value of exports. In another point of view based on the theory, the exchange rate that is experiencing appreciation causes the decrease of exports’ value and on the other hand, a depreciating exchange rate will cause exports to increase. However, before the pandemic the exchange rate that is weakened did not increase the value of exports significantly and during the COVID-19 pandemic the exchange rate fluctuated high which did not cause the value of exports to decline. Therefore, this study aims to determine whether there is a causal relationship between exchange rates and exports in Indonesia before and during the COVID-19 pandemic or not. This study used the Granger Causality test method to see the relationship between two variables. The results show there was no unidirectional or bidirectional causal relationship that before and during the pandemic.